2020
DOI: 10.3389/fphar.2020.00409
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Female and Male Human Detrusor Smooth Muscle Contraction by the Rac Inhibitors EHT1864 and NSC23766

Abstract: Introduction: Lower urinary tract symptoms (LUTS) due to overactive bladder (OAB) are caused by spontaneous detrusor contractions. Medical treatment with muscarinic receptor antagonists or b 3-adrenoceptor agonists aims to inhibit detrusor contractions, but overall results are unsatisfactory. Consequently, improved understanding of bladder smooth muscle contraction and identification of novel compounds for its inhibition are needed to develop alternative options. A role of the GTPase Rac1 for smooth muscle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 56 publications
3
14
0
2
Order By: Relevance
“…In both studies, inhibitory effects of NSC23766 were, however, at least partially related to a Rac‐independent antagonism of muscarinic receptors by NSC23766, in line with previous findings reporting this nonspecific feature of the presumed Rac inhibitor (Levay et al, 2013; B. Li et al, 2020; Rahman et al, 2014). Interestingly, the divergent pharmacological profiles of NSC23766 and EHT1863 became further manifest by different effects on TXA 2 induced contractions, which were inhibited by EHT1864, but not NSC23766 in human bladder tissues from both genders (B. Li et al, 2020). In rats with experimentally induced diabetes, Rac1 expression was reported to be up‐regulated in the detrusor, what was paralleled by pronounced inhibition of carbachol‐induced contractions by NSC23766 (Evcim et al, 2015).…”
Section: Rac Gtpases In Smooth Muscle Contractionsupporting
confidence: 89%
See 2 more Smart Citations
“…In both studies, inhibitory effects of NSC23766 were, however, at least partially related to a Rac‐independent antagonism of muscarinic receptors by NSC23766, in line with previous findings reporting this nonspecific feature of the presumed Rac inhibitor (Levay et al, 2013; B. Li et al, 2020; Rahman et al, 2014). Interestingly, the divergent pharmacological profiles of NSC23766 and EHT1863 became further manifest by different effects on TXA 2 induced contractions, which were inhibited by EHT1864, but not NSC23766 in human bladder tissues from both genders (B. Li et al, 2020). In rats with experimentally induced diabetes, Rac1 expression was reported to be up‐regulated in the detrusor, what was paralleled by pronounced inhibition of carbachol‐induced contractions by NSC23766 (Evcim et al, 2015).…”
Section: Rac Gtpases In Smooth Muscle Contractionsupporting
confidence: 89%
“…Regarding the urinary bladder, a pro‐contractile role of Rac1 in bladder smooth muscle has been confirmed using Rac1 knockout mice, where contractions induced by carbachol and high‐molar potassium chloride were reduced to wild types (Rahman et al, 2014). In line with these findings, NSC23766 and EHT1864 inhibited cholinergic contractions of bladder tissues from wild type mice and neurogenic and carbachol‐induced contractions of bladder tissues obtained from female and male patients undergoing radical cystectomy (B. Li et al, 2020; Rahman et al, 2014). In both studies, inhibitory effects of NSC23766 were, however, at least partially related to a Rac‐independent antagonism of muscarinic receptors by NSC23766, in line with previous findings reporting this nonspecific feature of the presumed Rac inhibitor (Levay et al, 2013; B. Li et al, 2020; Rahman et al, 2014).…”
Section: Rac Gtpases In Smooth Muscle Contractionsupporting
confidence: 53%
See 1 more Smart Citation
“…The growth inhibition of BC cells induced by EHT1864 is related to the dual inhibition of PI3K-AKT-mTORC1 and MEK-ERK pathways (179). Studies have shown that Rac1 plays an important role in the contraction of various smooth muscles, such as bronchial smooth muscle, bladder smooth muscle, and prostate smooth muscle (180)(181)(182)(183). Although both EHT1864 and NSC23766 are Rac1 inhibitors, they have different pharmacological mechanisms in the inhibition of different smooth muscles (182,184,185), and EHT1864 tends to perform better (186,187).…”
Section: General Rac1 Inhibitormentioning
confidence: 99%
“…Although β 3 -adrenoceptor agonists are recommended as an alternative option for treating storage symptoms 8 , increasing evidences are indicating that their efficacy do not exceed the muscarinic receptor antagonists, moreover, the long-term effect still remains inadequate 11 . Several studies have revealed that noncholinergic agonists, for example, thromboxane A 2 , prostanoids, and endothelin-1 may also cause detrusor contractions 12 , 13 , 14 , this may partially explain the unsatisfied efficacy of anticholinergics and β 3 -adrenoceptor agonists. Consequently, due to the unsatisfied efficacy and high discontinuation rates of the available pharmacological options, novel treatment strategies become more warranted than ever, and a more precise understanding of detrusor contraction is highly required.…”
Section: Introductionmentioning
confidence: 99%